Industrial enzyme production for the food and beverage industries: process scale up and scale down - Stocks, S.M.
Enzymes have many applications in the food and beverage industries and are produced in large quantities by large scale aerobic fermentation processes. Scale up of these fermentation processes is discussed in the context of process development for large scale enzyme production for the food and feed industry. Gassed agitated aerobic fermentations of differing rheological complexity are considered. Equations related to oxygen transfer and 'mixing' are presented and used to illustrate some non-intuitive phenomena that are often overlooked in consideration of 'scale up'. A 'scale down' mentality is presented where the ? nal production scale is de? ned and used to ? nd relevant conditions for experiments in smaller scale equipment. These results can then be used for development of empirical or mechanistic models to facilitate reduced risk on subsequent scale up. It is demonstrated that a perfect scale down cannot be accomplished and that scale up therefore remains an exercise in risk mitigation that is a mixture of both art and science.
Keywords: ENZYME PRODUCTION; FERMENTATION; MASS TRANSFER; MIXING; SCALE DOWN; SCALE UP; STIRRED TANK REACTOR